Fatty acid conjugation leads to length-dependent antimicrobial activity of a synthetic antibacterial peptide (Pep19-4LF) - Storck, Philip; Umstätter, Florian; Wohlfart, Sabrina; Domhan, Cornelius; Kleist, Christian; Werner, Julia; Brandenburg, Klaus; Zimmermann, Stefan; Haberkorn, Uwe; Mier, Walter; Uhl, Philipp (Antibiotics, 2020)
The increasing number of infections caused by multidrug-resistant bacteria requires an intensified search for new antibiotics. Pep19-4LF is a synthetic antimicrobial peptide (GKKYRRFRWKFKGKLFLFG) that was previously designed with the main focus on high antimicrobial activity. The hydrophobic motif, LFLFG, was found to be essential for antimicrobial activity. However, this motif shows several limitations such as aggregation in biological media, low solubility, and small yields in peptide synthesis. In order to obtain more appropriate peptide characteristics, the hydrophobic motif was replaced with fatty acids. For this purpose, a shortened variant of Pep19-4LF (Pep19-short; GKKYRRFRWKFKGK) was synthesized and covalently linked to saturated fatty acids of different chain lengths. The peptide conjugates were tested with respect to their antibacterial activity by microdilution experiments on different bacterial strains. The length of the fatty acid was found to be directly correlated to the antimicrobial activity up to an ideal chain length (undecanoic acid, C11:0). This conjugate showed high antimicrobial activity in absence of toxicity. Time-kill studies revealed a fast and bactericidal mode of action. Furthermore, the first in vivo experiments of the conjugate in rodents demonstrated pharmacokinetics appropriate for application as a drug. These results clearly indicate that the hydrophobic motif of the peptide can be replaced by a single fatty acid of medium length, simplifying the design of this antimicrobial peptide while retaining high antimicrobial activity in the absence of toxicity.
Gesehen am 15.02.2022